Does Low Socioeconomic Status Cause Individuals to Distrust the Healthcare Establishment? - Haschke, Cole; Cronje, Ruth J. (My University, 2019)
It is well known that individuals with low socioeconomic status have worse health outcomes compared to others. One reason is they can’t afford the medical costs of their care, but current thinking acknowledges that unmet social needs have an even more significant impact on downstream health outcomes. We wondered whether low-income individuals might also have attitudinal barriers to healthcare systems that stigmatize them, thus motivating them to avoid seeking necessary medical attention.
Color poster with text, images, and graphs.
Keywords: Socioeconomic factors; Medical care; Trust; Posters